Decision-Making in the Moments Before Death: Challenges in Prehospital Care. (4th May 2019) - Waldrop, Deborah P.; McGinley, Jacqueline M.; Dailey, Michael W.; Clemency, Brian
Abstract: Background: The primary charge of Emergency Medical Services (EMS) is to save lives. However, EMS personnel are frequently called to scenes where prolonging life may not be the primary goal. When someone is nearing death, family members may feel compelled to call 9-1-1 because they are feeling uncertain about how to manage symptoms at the end of life.Objective : We sought to explore prehospital providers' perspectives on how the awareness of dying and documentation of end-of-life wishes influence decision-making on emergency calls near the end of life.Methods: The study design was exploratory, descriptive, and cross-sectional. Qualitative methods were chosen to explore participants' perspectives in their own words. In-depth in-person interviews were conducted with 43 EMS providers. Interviews were audio recorded and professionally transcribed. Interview transcripts were entered in Atlas.ti for data management and coding. The analysis was deductive and guided by a conceptual model of 4 contexts of end-of-life decision-making that is not setting-specific, but has been applied to prehospital care in this study.Results: The findings illustrate the relationship between awareness of dying and documentation of wishes in EMS calls. The 4 decisional contexts are: (1) Awareness of Dying-Wishes Documented : Families were prepared but validation and/or support was needed in the moment; (2) Awareness of Dying-Wishes Undocumented : EMS must initiate treatment, medical control guidance was needed; (3) Unaware of Dying-Wishes Documented : Shock, expectation that EMS can stop the dying; and (4) Unaware of Dying-Wishes Undocumented : Families were unprepared, uncertain, frantic. Each context is illustrated by representative quotes from participants. Discordance and conflict was found in each decisional context.Conclusions: This study illustrates that EMS providers are acutely aware of the impact of their decisions and actions on families at the end of life. How emergency calls near the end of life are handled influences how people die, whether their preferences are honored, and the appropriate use of ambulance transport and ED care. The findings highlight how the intersection of awareness of dying and documentation of wishes influence prehospital decision-making in end-of-life emergencies and demonstrate the key role EMS providers have in this critical period.